2013
DOI: 10.1158/1078-0432.ccr-12-3175
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways: Current Role and Future Directions of the Retinoic Acid Pathway in Cancer Prevention and Treatment

Abstract: Retinoids and their naturally metabolized and synthetic products (e.g. all-trans retinoic acid, 13-cis retinoic acid, bexarotene) induce differentiation in various cell types. Retinoids exert their actions mainly through binding to the nuclear retinoic acid receptors (α, β, γ), which are transcriptional and homeostatic regulators whose functions are often compromised early in neoplastic transformation. The retinoids have been investigated extensively for their utility in cancer prevention and treatment. Succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
135
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(147 citation statements)
references
References 74 publications
4
135
0
8
Order By: Relevance
“…[31][32][33] For example, Kaposi sarcoma and headand-neck cancer have already been treated with ATRA-based therapies. 34,35 Retinoids are clearly a promising class of compounds that will greatly enlarge our arsenal in the fight against cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] For example, Kaposi sarcoma and headand-neck cancer have already been treated with ATRA-based therapies. 34,35 Retinoids are clearly a promising class of compounds that will greatly enlarge our arsenal in the fight against cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that retinoic acid and its products, such as all-trans retinoic acid (ATRA), urge the differentiation of multiple types of stem cells, including the stem cells that exist in BC (130,131). On the other hand, ATRA has been used in a clinical trial and its efficacy was limited (132), possibly because of the epigenetic knock-out of the retinoic acid receptor (RAR)-β (133). Recent studies have shown that HDAC inhibitors have the ability to re-express RAR-β, so they restore the sensitivity of the cells to treatment (134)(135)(136).…”
Section: Hdac Inhibitors As Anti-cancer Agentsmentioning
confidence: 99%
“…RARB is one of critical ligand-regulated transcription factors to centralize the cancer cell growth and metastasis through the RA and retinoid signaling pathways [11]. RARB was suggested as a potential therapeutic target to protect from solid tumors by the frequent epigenetic silencing of RARB [12]. Comprehensive expression of retinoic acid receptors in non-small cell lung cancer tissue was about up to 60% lower than in the normal [13], while extensive retinoidbased therapies, e.g.…”
Section: Discussionmentioning
confidence: 99%